Clinical Characteristics of Gestational Trophoblastic Neoplasia: A 15-Year Hospital-Based Study. Issue 1 (January 2016) - Sun, Rong; Zhang, Ye; Zheng, Wei; Tian, Quan; An, Ruifang; Xue, Yan
Abstract : Objective: To analyze the clinical profile of invasive mole (IM) and choriocarcinoma (CCA) in the past 15 years in Western China. Materials and Methods: A retrospective study was performed on 221 patients with IM and 70 patients with CCA treated in the First Affiliated Hospital of Xi'an Jiaotong University from 1994 to 2009. Patients were assigned into 3 groups by 5 years, and the clinical characteristics were compared among these groups. Results: The incidence was not significantly changed in the past 15 years, whereas the mean age of gestational trophoblastic neoplasia (GTN) was increased significantly, especially for the patients 40 years or older. The symptoms of the patients with GTN did not show significant variation, but the number of patients with CCA without clinical symptoms was increased significantly. The mean values of beta human chorionic gonadotropin in the patients with IM and those with CCA were 459.43 and 661.70 mIu/L, respectively, and the size of uterine lesion was concentrated at 4 cm or less in both the patients with IM and those with CCA, without significant differences. Conclusions: In the past 15 years, the incidence of GTN was still higher than in other countries from 1994 to 2009, and the mean age of patients with GTN was increased significantly, especially for the patients older than 40 years. Furthermore, patients with no clinical manifestations increased significantly, which should be paid more attention in the future works. Serum level of beta human chorionic gonadotropin and pelvic ultrasonography are still 2 important indexes for diagnosing and monitoring condition of GTN.